2016
DOI: 10.4172/2157-7110.1000589
|View full text |Cite
|
Sign up to set email alerts
|

Colour Intensity, Polyphenol Content and Antibacterial Capacity of Unheated and Heat-Treated Sahara Honey

Abstract: The objective of this research work was to evaluate the effect of heat processing on antibacterial capacity of Sahara honey (SH). Various thermal treatments were carried out at 25°C, 50°C, 75°C and 100°C for 15 min, 30 min, and 60 min, and the parameters were determined: colour intensity, phenolic contents and antibacterial activity of two species of bacteria (Staphylococcus aureus and Pseudomonas aeruginosa). The total phenolic contents in honey samples varied from 0.55 and 1.54 mg of gallic acid equivalent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Its two main sugars are glucose and fructose, but other di- and trisaccharides are also present [ 1 ]. Depending on their botanical and geographical origin, vitamins, minerals, phenolic acids, flavonoids, organic acids and amino acids are present in honey in different amounts [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Origin also has an effect on the sensory profile of honeys [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its two main sugars are glucose and fructose, but other di- and trisaccharides are also present [ 1 ]. Depending on their botanical and geographical origin, vitamins, minerals, phenolic acids, flavonoids, organic acids and amino acids are present in honey in different amounts [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Origin also has an effect on the sensory profile of honeys [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The generated OH˙ radicals are powerful but short-lived oxidants that cause proteins and lipid peroxidation and DNA and RNA degradation in bacterial cells [ 7 , 24 , 27 ]. However, it also should be noted that many reports have not confirmed the correlation between total phenolic content or antioxidant activity and antimicrobial potential of the product [ 30 , 31 ]. Thus, in our opinion, the crucial role of polyphenols in the generation of OH˙ radicals is not a complete explanation of the role of phytochemicals in the antimicrobial activity of all hydrogen peroxide dependent honeys.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was suggested that CI could be associated with phenolic and flavonoid compounds. The higher the CI values, the higher the phenolic and flavonoid contents are (Moniruzzaman et al ., ; Ahmed et al ., ). The CI values of all longan honey samples were in the range of 0.658 ‐ 0.663 AU, which were similar to the CI reported by the Kashmir honey (El Sohaimy et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Absorbance was measured at wavelengths of 460 nm and 720 nm. Colour intensity (CI) was calculated by subtraction of the absorbance at 720 nm from that at 460 nm (Ahmed et al ., ). Colour was measured in CIE L*a*b* system using Konica Minolta Chroma Meters (model CR‐400/CR‐410, Konica Minolta Inc., Osaka, Japan) according to the method used by Viuda‐Martos et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation